Eccentric Fatigue Modulates Stretch-shortening Cycle Effectiveness – A Possible Role in Lower Limb Overuse Injuries - Debenham, J.; Travers, M.; Gibson, W.; Campbell, Amity; Allison, Garry (2016)
The role of fatigue in injury development is an important consideration for clinicians. In particular, the role of eccentric fatigue in stretch-shortening cycle (SSC) activities may be linked to lower limb overuse conditions. The purpose of this study was to explore the influence of ankle plantarflexor eccentric fatigue on SSC effectiveness during a hopping task in healthy volunteers. 11 healthy volunteers (23.2±6.7 years) performed a sub-maximal hopping task on a custom-built sledge system. 3D motion capture and surface EMG were utilised to measure lower limb stiffness, temporal kinematic measures and muscle timing measures at baseline and immediately following an eccentric fatigue protocol. A linear mixed model was used to test whether measures differed between conditions. Compared to baseline, eccentric fatigue induced increased stiffness during the hopping task (+ 15.3%; P<0.001). Furthermore, ankle stretch amplitude decreased (– 9.1%; P<0.001), whilst all other ankle kinematic measures remained unchanged. These changes were accompanied by a temporal shift in onset of activity in soleus and tibialis anterior muscles (– 4.6 to – 8.5%; p<0.001). These findings indicate that eccentric fatigue alters SSC effectiveness in healthy volunteers. These findings may be applied to inform pathogenetic models of overuse injury development.